Convolution Neural Network Based Enhanced Learning Classification Using Privileged Information - Dhaduk, Hardikkumar M; Mallikarjuna Shastry , PM (International Journal of Computer Sciences and Engineering, 2019)
The accuracy of data-driven teaching methods is often unsatisfactory when training data are insufficient either in amount or quality. Usually incorporate privileged information (PI), tags, properties or attributes manually labeled to improve the learning of classification. The manual labeling process, however, takes time and works intensively. In addition, manually labeled privileged information may not be rich Sufficient due to personal knowledge limitations. In this approach, classifier learning is enhanced by exploring untagged corporate privileged information (PI), which can effectively eliminate reliance on manually labeled data and enhance privileged information. We treat each selected privileged information as a subcategory in detail and for each subcategory we learn one classifier independently. Classifiers are integrated for all sub-categories to form a more powerful category classifier. In this CNN classifier approach, in particular, to learn the optimum output based on the pictures chosen. The superiority of this proposed approach is demonstrated by extensive experiments on two benchmark data sets.